CHEMICAL CONTENT OF SAUSSUREA INVOLUCRATA KAR. ET KIR. STUDY WHICH GROWS IN KAZAKHSTAN - A. N. Zhabaeva; H. I. Itzhanova; M. Yu. Kurapova; A. L. Ebel; A. N. Kupriyanov; S. M. Adekenov (Фармация и фармакология (Пятигорск))
The article shows the results of Saussurea involucrata Kar. et Kir. chemical content study which grows in Kazakhstan